2022
DOI: 10.3389/fpls.2022.993682
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of carotenoid metabolites and transcriptome identifies key genes controlling carotenoid compositions and content in sweetpotato tuberous roots (Ipomoea batatas L.)

Abstract: Sweetpotato (Ipomoea batatas L.) with different depths of yellow color contains different compositions of carotenoids, which are beneficial for human health. In this study, we performed an integrated analysis of metabolomic and transcriptomic to identify key genes playing a major role in carotenoid coloration in sweetpotato tuberous roots. Herein, 14 carotenoids were identified in five sweetpotatoes. Orange-red and orange cultivars were dominated by β-carotene (385.33 μg/g and 85.07 μg/g), yellow cultivar had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As high-value and health-promoting natural products, carotenoid contents and their compositions were well characterized in the tuberous roots of sweetpotato [28,[31][32][33][34]. However, there is a lack of data describing the dynamic changes in carotenoid profiles during different tuberous root developmental stages of sweetpotato varieties with different flesh colors.…”
Section: Three Varieties Of Sweetpotato With Different Flesh Colors R...mentioning
confidence: 99%
See 3 more Smart Citations
“…As high-value and health-promoting natural products, carotenoid contents and their compositions were well characterized in the tuberous roots of sweetpotato [28,[31][32][33][34]. However, there is a lack of data describing the dynamic changes in carotenoid profiles during different tuberous root developmental stages of sweetpotato varieties with different flesh colors.…”
Section: Three Varieties Of Sweetpotato With Different Flesh Colors R...mentioning
confidence: 99%
“…UPLC-APCI-MS/MS analysis has shown that β-cryptoxanthin and β-carotene are the predominant carotenoids in yellow-fleshed sweetpotato "Baishu" and white-fleshed sweetpotato "shangshu19, " respectively [32]. UPLC-APCI-MS/MS analysis has also determined that β-cryptoxanthin and lutein are enriched in yellowfleshed sweetpotato "Jieshu 95-16" and white-fleshed sweetpotato "shangshu19, " respectively [31]. These inconsistent results from different studies could be related to variations in genetic inheritance, growing environments [36], and analytical methods.…”
Section: Three Varieties Of Sweetpotato With Different Flesh Colors R...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sweet potato flesh appears white, yellow, orange, and purple in different colors due to the accumulation of pigment content. The diverse components and compositions of carotenoids contribute varying hues to yellow and orange sweet potatoes [3,4]. These varieties are highly advantageous for human health due to their elevated carotenoid content, which serves as a significant source of vitamin A [5,6].…”
Section: Introductionmentioning
confidence: 99%